2013
DOI: 10.1159/000355368
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Early Psychosocial Intervention in Alzheimer's Disease

Abstract: Background/Aim: To investigate the impact of early psychosocial intervention aimed at patients with Alzheimer's disease (AD) and their caregivers on resource use and costs from a societal perspective. Methods: Dyads of patients and their primary caregiver were randomised to intervention (n = 163) or control (n = 167) and followed for 3 years. Health care use was extracted from national registers, and the Resource Utilisation in Dementia questionnaire was used to measure informal care and productivity loss. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…It is worth noting that indirect costs including caregiver time lost, account for ∼68% of total cost, followed by the direct medical costs (24.7%) which include hospitalizations [17]. Similar estimates of cost patterns among dementia patients paired with their caregivers were obtained in an intervention study conducted in Denmark [35] and another multi-country large cross-sectional study (France, Germany, and UK) [36]. In the latter study, while >50% of total societal costs resulted from caregiver informal care, those were increased by co-morbidities and physical limitations, while lower total societal costs were associated with caregiver not working for pay and patient living alone or living with spouse.…”
Section: Discussionmentioning
confidence: 84%
“…It is worth noting that indirect costs including caregiver time lost, account for ∼68% of total cost, followed by the direct medical costs (24.7%) which include hospitalizations [17]. Similar estimates of cost patterns among dementia patients paired with their caregivers were obtained in an intervention study conducted in Denmark [35] and another multi-country large cross-sectional study (France, Germany, and UK) [36]. In the latter study, while >50% of total societal costs resulted from caregiver informal care, those were increased by co-morbidities and physical limitations, while lower total societal costs were associated with caregiver not working for pay and patient living alone or living with spouse.…”
Section: Discussionmentioning
confidence: 84%
“… 82% Jansen [ 56 ], 2011 Dyads Case management, include 2 home visits, personal care plan, family-meeting, etc. 81.8% Søgaard [ 51 ], 2014 Dyads Multi-component intervention, include disease education, communication skills, et al 80% Prick [ 24 ], 2014 Dyads Multi-component psychosocial intervention, exercise and support 77.2% Joling [ 67 ], 2013 Dyads Multi-component family meetings intervention, include psycho-education, problem solving techniques, emotional and instrumental support 77% Roberts [ 34 ], 2009 Dyads Social and psychological intervention, include individual and family consultations, support group, weekly four-session education 74% Whitlatch [ 25 ], 2006 Dyads Multi-component EDDI dyadic program, include emotional support, communication skills, Dementia education 65% Orsulic-Jeras [ 60 ], 2016 Dyads Social and psychological intervention, Dyadic counseling-based, include support activities, and education. 65% Woods [ 64 ], 2016 Dyads Multi-component intervention, RYCT program.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-one high- and moderate-quality studies reported data on participants’ completion rate with the interventions, ranging from high to low levels. Sixteen papers showed high completion rate (80% participants completed the intervention), including 5 social [ 36 , 37 , 54 , 57 , 63 ], one cognitive [ 40 ], one physical [ 45 ] and 9 other psychosocial interventions [ 17 , 44 , 46 , 49 , 51 , 53 , 55 , 56 , 66 ]. Fourteen showed moderate completion rate (60–79% participants completed), including 4 cognitive [ 48 , 50 , 61 , 62 ], one social [ 65 ], one physical [ 59 ] and 8 other psychosocial interventions [ 24 , 25 , 35 , 47 , 52 , 58 , 60 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the usual challenges associated with assessing the effects of social care aimed at community-dwelling individuals, relatively high response rates were obtained. The responses were supported with detailed register data from national registries to provide a comprehensive data set that had been thoroughly analysed and separately interpreted before it was synthesised in this paper 5 6 8 13 14…”
Section: Discussionmentioning
confidence: 99%